Morphological features of the skin microcirculatory bed in patients with psoriasis and essential hypertension - Makurina G.I. (Морфологія, 2016)
Background. Many questions about pathomorphogenesis of damage of the skin microcirculatory bed in patients with psoriasis and hypertension on the background of the skin age changes require clarification and further advance. Objective. The aim of research is to determine the damages of the skin microcirculatory bed in psoriasis patients, depending on the presence or absence of hypertension. Methods. In 60 patients with active psoriasis with and without hypertension skin biopsies were studied using light-optical microscopy. In quantitative morphological study the maximum and minimum overall length of basal, spinous and granular layers of the epidermis were explored, numerical density of nuclei and mitotic index of keratinocytes were calculated. Results. It was found that the morphological basis of damages of the skin microcirculatory bed in patients with psoriasis and hypertension is a complex of general vascular changes: hyperproliferation of microvascular wall cells (endothelial cells, pericytes, smooth myocytes) with the development of hyalinosis and elastofibrosis of arterioles, disseminated abuse of angioarchitectonics of arterioles and intrapapillary hemocapillaries. It triggers a cascade of typical pathomorphological changes of significantly higher intensity than the skin lesions in psoriasis patients without hypertension. Conclusion. Comorbid morphogenesis causes dermal damage in patients with psoriasis and hypertension: significant interstitial edema of papillary layer; perifocal leukocyte infiltration, exudation, extravasations, plasmorrhage consisting of dermal papillae; lymphostasis and local extension of lymphatic drainage; erythrocyte sludging, erythrodiapedesis, hemorrhage; strengthening of endothelial dysfunction with activation of vascular-platelet hemostasis. Citation: Makurina GI. [Morphological features of the skin microcirculatory bed in patients with psoriasis and essential hypertension]. Morphologia. 2016;10(1):38-48. Ukrainian.